THEMATIC PROGRESSION IN RECOUNT TEXT WRITTEN BY THE TENTH GRADE STUDENTS - Nasution, Tia Pahrani; Ginting, Siti Aisah; Oktora, Maya (Universitas Negeri Medan, 2019)
This Study was about the theme, rheme and thematic progression of students ' recount text of the tenth grade at SMA Budisatrya Medan. The aims of this study were (1) to investigate thematic progression pattern used in recount text (2) to investigate the reason why the students used thematic progression in the way they did. This study was conducted by using descriptive qualitative method. The data in this study were clauses of students ˜recount text. The instruments of collecting data were elicitation technique and interview. The data was analyzed by using interactive model technique of Miles, Huberman and Saldana (2014). The results of this study were the following. (1) There were two patterns of thematic progression used in students™ recount text, they were Theme Reiteration/Constant Theme Pattern (TR/CTP), and Zig - zag / Linear Theme Pattem ( Zig - zag / LTP). (2) The reason to use the thematic progression by the students, they were: (a) the students were lack of knowledge about the use of the thematic progression, (b) they are also less interested in writing. (c) The students got resources from English teacher™s explanation and (d) the students got resources from reading recount text.Keywords: Theme , Rheme , Thematic Progression , Recount text .